Formulasi Ekstrak Etanol Ranting Patah Tulang (Euphorbia tirucalli (Linn)) sebagai Foot Spray terhadap Bakteri Staphylococcus aureus - Nur Islamyah Maulana; Wahyuddin Jumardin; Hilmiati Wahid (Jurnal Pengabdian Masyarakat, 2025)
Foot odor is a common problem due to the activity of bacteria such as Staphylococcus aureus in humid conditions of the feet promoting bacterial growth and metabolic activity. Problems like this can be overcome by utilizing antibacterial preparations to suppress the formation of bacteria that produce foot odor, namely anti-foot spray preparations or foot sprays. This study aims to formulate ethanol extract of broken twigs (Euphorbia tirucalli (Linn)) as a foot spray preparation that is physically and chemically stable and has antibacterial activity. The method used is quantitative research used in formulating foot spray preparations for ethanol extract of broken twigs (Euphorbia tirucalli (Linn)). Foot spray preparations are made in 4 formulations, namely negative control, 5%, 7%, and 9% concentrations. Preparation evaluation includes organoleptic test, pH test, homogeneity test, viscosity test, dry time test, and spray pattern test. Next, an irritation test and an antibacterial activity test were carried out. The results showed that before and after the cycling test there was no change with a p>0.05 value. Ethanol extract of broken twigs (Euphorbia tirucalli (Linn)) contains flavonoids, tannins, and steroids. It can be concluded that foot spray preparations show physical stability and antibacterial effectiveness, with a concentration of 9% having an inhibition zone of 12.55 mm which is the most effective against Staphylococcus aureus bacteria.